THYROTOXICOSIS IN PATIENTS WITH HYDATID MOLE - Rahadianto Rahadianto; Maimun Z. Arthamin (Oceana Biomedicina Journal, 2021)
Hydatid Mole, also often called grape pregnancy, is a pregnancy characterized by abnormal trophoblast development. The incidence of hydatidiform mole per 1,000 pregnancies occurs in Asia. In Indonesia, in 2002 cases of hydatidiform mole were found 1: 123 pregnancy, and in 2003 found cases of hydatidiform mole 1: 245 pregnancy. While the results of research conducted in the same place in 2012-2013 obtained 39 cases of hydatidiform mole that were distributed based on age groups, parity, education, and hemoglobin levels of patients. Trophoblastic hyperthyroidism is a rare case but can be life threatening. Alpha subunit-human chorionic gonadotropin (HCG) is similar to alpha sub-unit-thyroid stimulating hormone (TSH). If HCG concentrations increase over a long period of time, it can increase free T4 and free T3 levels. In this patient there was also a sudden onset of hypertension, proteinuria 3+, ketonuria 3+, hematuria 3+, leukosituria 1+, bacteriuria which could possibly be caused by the occurrence of a pre-eclampsia or UTI in this patient. The cause of pre-eclampsia in molar pregnancy is thought to be due to excessive levels of soluble fms-like tyrosine kinase 1 (sFlt1) in the circulation, an endogenous anti-angiogenic protein that enters the maternal circulation after overproduction in the placenta.